A hybrid power management schema for multi-tier data centres. (4th June 2019) - Azimzadeh, Aryan; Shoja, Babak Maleki; Tabrizi, Nasseh
Data centres play an important role in the operation and management of IT infrastructures but because of their huge power consumption, it raises an issue of great concern as it relates to global warming. This paper explores the sleep state of data centres' servers under specific conditions such as setup time and identifies an optimal number of servers potentially to increase energy efficiency. We use a dynamic power management policy-based model with the optimal number of servers that is required in each tier while increasing servers' setup time after sleep mode. The reactive approach is used to validate the results and energy efficiency by calculating the average power consumption of each server under specific sleep mode and setup time. Our method uses average power consumption to calculate the normalised-performance-per-watt in order to evaluate the power efficiency. The results indicate that the schema reported in this paper can improve power efficiency in data centres with high setup time servers.